2017
DOI: 10.13057/nusbiosci/n090114
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Water quality improvement of Nile tilapia and catfish polyculture in aquaponics system

Abstract: Abstract. Hasan Z, Dhahiyat Y, Andriani Y, Zidni I. 2016. Water quality improvement of Nile tilapia and catfish polyculture in aquaponics system. Nusantara . Research on the improvement of polyculture water quality in aquaponics system was conducted from July 2014 to August 2014. This study aims to improve the water quality in Nile tilapia and catfish polyculture by applying the aquaponics system. The results show that several water quality parameters increase, such as dissolved oxygen, ammonia, and nitrate. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 1 publication
(1 reference statement)
1
6
0
2
Order By: Relevance
“…82 of 2001 defines the safe concentration of phosphate in Class II and Class III water as 0.2 mg/L and 1 mg/L, respectively. This is in line with the results of research Hasan et al (2017) which states that the treatment with aquatic plants in aquaponic reduce the phosphate concentration, due to phosphate being used by the plant as a nutrient.…”
Section: Water Quality Parameterssupporting
confidence: 89%
See 1 more Smart Citation
“…82 of 2001 defines the safe concentration of phosphate in Class II and Class III water as 0.2 mg/L and 1 mg/L, respectively. This is in line with the results of research Hasan et al (2017) which states that the treatment with aquatic plants in aquaponic reduce the phosphate concentration, due to phosphate being used by the plant as a nutrient.…”
Section: Water Quality Parameterssupporting
confidence: 89%
“…Andriani et al (2017) showed that the length of water-spinach reached 20-25 cm, while on lettuce the harvesting size was reached at the fourth week with average length 27.28 cm. The Chinese spinach weights increase in an aquaponic biofilter system is influenced by the degree of utilization of nutrient derived from the degradation of residual feed and fish metabolism waste product by nitrifying bacteria .…”
Section: Plant Growthmentioning
confidence: 99%
“…Based on Ebeling et al (2006), good phosphate concentration in fish culture was 0.2-1 mg/L. Decreased phosphate concentration in the culture media in this study was thought due to water spinach absorption as a nutrient intake (Lestari et al, 2015;Hasan et al, 2017). A significant increase in phosphate concentration occurred in the third observation, which may occur due to related to decreased phosphate absorption by matured plants that were ready to be harvested (Wasonowati et al, 2013).…”
Section: Discussionmentioning
confidence: 70%
“…Konsep dasar pembuatan akuaponik adalah adanya hubungan saling menguntungkan antara tanaman dan ikan dimana tanaman mendapatkan nutrisi untuk pertumbuhannya dari feses ikan yang larut dalam air, sedangkan akar tanaman berguna sebagai filter biologis sehingga menghailkan kuallitas air yang baik bagi kelangsungan hidup ikan (Hasan et al, 2017). Desain sistem akuaponik dapat dibuat sesuai dengan kondisi lahan, jenis ikan dan tanaman yang dipelihara (Somerville et al, 2014).…”
Section: Jenis-jenis Dan Konstruksi Akuaponikunclassified